2012
DOI: 10.1517/17425255.2012.688026
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic evaluation of rivaroxaban for the treatment of acute coronary syndromes

Abstract: The mortality benefit with low-dose rivaroxaban in ACS patients was first demonstrated in ATLAS ACS2 TIMI-51 trial. With its rapid oral bioavailability, predictable PK, low drug-drug interaction and no need for monitoring, the use of low-dose rivaroxaban in addition to dual antiplatelet therapy offers an appealing new option in improving outcomes following ACS in the modern era of novel oral FXa inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 58 publications
3
9
0
Order By: Relevance
“…Furthermore, Mueck et al reported that the PT correlated almost linearly with rivaroxaban concentrations below 500 ng/ml 37 . In addition, a linear intercept model with a declining exponent and correlation of PT with the logarithm of the rivaroxaban plasma concentration was reported previously 27,30,38 …”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, Mueck et al reported that the PT correlated almost linearly with rivaroxaban concentrations below 500 ng/ml 37 . In addition, a linear intercept model with a declining exponent and correlation of PT with the logarithm of the rivaroxaban plasma concentration was reported previously 27,30,38 …”
Section: Discussionmentioning
confidence: 83%
“…It has dose-proportional pharmacokinetics with an oral bioavailability of approximately 80% [37]. The half-life is 5-13 h (5-9 h in the young and 11-13 h in the elderly) and the time to peak concentration in plasma is 2-4 h, which correlates well with the time for maximum inhibition of factor Xa [38]. The inhibition of factor Xa persists for up to 24 h after administration of a dose of rivaroxaban.…”
Section: Oral Factor Xa Inhibitors In Acsmentioning
confidence: 99%
“…a creatine clearance of <15 ml/min), and the dose needs to be adjusted in patients with advanced renal insufficiency (i.e. a creatine clearance of 15-29 ml/min) [38,40]. …”
Section: Oral Factor Xa Inhibitors In Acsmentioning
confidence: 99%
“…drug-drug interactions, metabolism, naringenin, pharmacokinetic, rivaroxaban F I G U R E 1 Chemical structures of rivaroxaban, rivaroxaban metabolite M2, M1, naringenin, and diazepam inducers or inhibitors of CYP3A4, 12,23,24 the purpose of the current study is to evaluate whether some drug-drug interactions are existed between naringenin and rivaroxaban in rats both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that naringenin can influence the pharmacokinetics and metabolism of other drugs when co‐administrated with those drugs metabolized by CYP3A4 (such as tofacitinib, ibrutinib, and felodipine) 20–22 . Considering that rivaroxaban can be influenced by inducers or inhibitors of CYP3A4, 12,23,24 the purpose of the current study is to evaluate whether some drug–drug interactions are existed between naringenin and rivaroxaban in rats both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%